SOCIO-ECONOMIC FACTORS AFFECTING CORN FARMING INCOME AND ITS CONTRIBUTION TO HOUSEHOLD INCOME - Jelita, Priscila V.; Nendissa, Doppy Roy; Bani, Aplonia (Buletin Ilmiah Impas, 2025)
Maize plays an important role as a source of food and income for farmers in East Nusa Tenggara (NTT), Indonesia. However, maize is not yet a major economic pillar for rural households. This study aims to analyze the influence of socioeconomic factors on maize farming income and assess its contribution to household income in Pukdale Village, East Kupang Subdistrict, Kupang Regency. Although maize is the main agricultural commodity in this area, it has not yet provided an optimal economic impact for farming families. This study used a quantitative approach using a survey and multiple linear regression analysis. The sample consisted of 60 maize farmers randomly selected from a total population of 400 farmers. Primary data were collected through structured questionnaires and direct interviews. The results showed the regression equation model as follows: Ln Y = 19.923 + 0.232 Ln_X1 + 0.076 Ln_X2 + 0.480 Ln_X3 + 1.284 Ln_X4 + 0.332 Ln_X5 - 0.343 Ln_X6. Simultaneously (f test) together the independent variables have a significant effect on corn farm income. Partial test (t test) shows that the variables of land area and fertilizer price have a significant effect on corn farm income, while age, non-formal education, farming experience and labor have no significant effect. The coefficient of determination (Adjusted R2) of 68.4% shows that the independent variables are able to explain the dependent variable, corn farming income. The contribution of maize farming to household income is 44.00% and is classified as moderate.